Influence of cortisol cosecretion on non-ACTH-stimulated adrenal venous sampling in primary aldosteronism: a retrospective cohort study. Issue 5 (29th September 2022) - Heinrich, Daniel Alexander; Quinkler, Marcus; Adolf, Christian; Handgriff, Laura; Müller, Lisa; Schneider, Holger; Sturm, Lisa; Künzel, Heike; Seidensticker, Max; Deniz, Sinan; Ladurner, Roland; Beuschlein, Felix; et al.
Abstract: Objective: Cortisol measurements are essential for the interpretation of adrenal venous samplings (AVS) in primary aldosteronism (PA). Cortisol cosecretion may influence AVS indices. We aimed to investigate whether cortisol cosecretion affects non-adrenocorticotrophic hormone (ACTH)-stimulated AVS results. Design: Retrospective cohort study at a tertiary referral center. Methods: We analyzed 278 PA patients who underwent non-ACTH-stimulated AVS and had undergone at least a 1-mg dexamethasone suppression test (DST). Subsets underwent additional late-night salivary cortisol (LSC) and/or 24-h urinary free cortisol (UFC) measurements. Patients were studied from 2013 to 2020 with follow-up data of 6 months following adrenalectomy or mineralocorticoid antagonist therapy initiation. We analyzed AVS parameters including adrenal vein aldosterone/cortisol ratios, selectivity, lateralization (LI) and contralateral suppression indices and post-operative ACTH-stimulation. We classified outcomes according to the primary aldosteronism surgical outcome (PASO) criteria. Results: Among the patients, 18.9% had a pathological DST result (1.9–5 µg/dL: n = 44 (15.8%); >5 µg/dL: n = 8 (2.9%)). Comparison of AVS results stratified according to the 1-mg DST (≤1.8 vs >1.8 µg/dL: P = 0.499; ≤1.8 vs 1.8 ≤ 5 vs >5 µg/dL: P = 0.811) showed no difference. Lateralized cases with post DST serum cortisol values > 5 µg/dL had lower LI (≤1.8 µg/dL: 11.11 (5.36; 26.76) vs 1.9–5 µg/dL: 11.76 (4.9; 31.88) vs >5 µg/dL: 2.58 (1.67; 3.3); P = 0.008). PASO outcome was not different according to cortisol cosecretion. Conclusions: Marked cortisol cosecretion has the potential to influence non-ACTH-stimulated AVS results. While this could result in falsely classified lateralized cases as bilateral, further analysis of substitutes for cortisol are required to unmask effects on clinical outcome.